2015
DOI: 10.1371/journal.pone.0130961
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological Distress in the Hospital Setting: A Comparison between Native Dutch and Immigrant Patients

Abstract: BackgroundPrevalence of psychological distress (i.e. depressive and anxiety symptoms) in medically ill patients is high. Research in the general population shows a higher prevalence of psychological distress among immigrants compared to natives. Our aim was to examine the prevalence of psychological distress in the hospital setting comparing immigrant and native Dutch patients and first and second generation immigrant patients.MethodsPrevalence of psychological distress was assessed using the extended Kessler-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 31 publications
3
8
1
13
Order By: Relevance
“…In line with findings regarding depression, the overall prevalence of anxiety in a Dutch general hospital setting was 51.7% for ethnic minorities and 36.6% in native Dutch [ 18 ]. In a large population based sample in the US, anxiety was related to ethnicity in patients with diabetes [ 23 ].…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…In line with findings regarding depression, the overall prevalence of anxiety in a Dutch general hospital setting was 51.7% for ethnic minorities and 36.6% in native Dutch [ 18 ]. In a large population based sample in the US, anxiety was related to ethnicity in patients with diabetes [ 23 ].…”
Section: Introductionsupporting
confidence: 76%
“…We hypothesized that all ethnic minorities would report higher levels of emotional distress in comparison to native Dutch persons and that in particular Turkish and Moroccan persons would report high levels of depression and anxiety [18]. As to the between-ethnic differences in diabetes-distress we had no hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows immigrant dialysis patients have a higher prevalence of depressive symptoms compared to native Dutch dialysis patients. These results are comparable with other European studies, which also found a higher prevalence in immigrant patients compared to native Dutch [6, 7, 32, 33]. US studies indicate that Black dialysis patients have a higher prevalence of depressive symptoms compared to White dialysis patients [15, 34, 35].…”
Section: Discussionsupporting
confidence: 88%
“…First, cohort studies and registry data have shown that ethnicity influences the prevalence rate of depression. Ethnic minority groups seem to have a higher burden of depressive symptoms in the dialysis population [7, 35].…”
Section: Discussionmentioning
confidence: 99%